IMPLEMENTATION OF NETWORK AUTOMATION USING ANSIBLE TO CONFIGURE ROUTING PROTOCOL IN CISCO AND MIKROTIK ROUTER WITH RASPBERRY PI - Muhammad Fauzi Islami; Purnawarman Musa; Missa Lamsani (Jurnal Ilmiah KOMPUTASI, 2020)
Network Engineering is never separated with configuration which is themain task must be commited in the purpose to put it into function. As we know,to configure some devices either server, switch, or router have some methods if weobserve by how we communicate to the system themselves. We can use the conso-le port to communicate with, using telnet to communicate remotely, or even usingSSH if we want to communicate remotely and also securely with all of the infor-mation is encrypted. Generally, the conventional method such as the methods hasjust explained before is always be used. The promblem has not come yet since thereare just 1 until 5 devices, but how about 100 devices ? We have to log in to the ne-twork devices one by one. It is exhausting and very inefficient in time. This paperis ilustrating a new methods in configuring network devices by using automation,reducing time for equipment configuration and easier to maintenance. It reduceshuman error in configuration syntaxes and how the way the device is configured.The innovation is going to make it happen. There are tools to do this tasks such as,ansible and terraform. In this paper, ansible is chosen because of its simplicity.